2013
DOI: 10.1186/1471-2164-14-391
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal nucleosome positioning in vivo and in vitro is directed by primary sequence motifs

Abstract: BackgroundHistone wrapping of DNA into nucleosomes almost certainly evolved in the Archaea, and predates Eukaryotes. In Eukaryotes, nucleosome positioning plays a central role in regulating gene expression and is directed by primary sequence motifs that together form a nucleosome positioning code. The experiments reported were undertaken to determine if archaeal histone assembly conforms to the nucleosome positioning code.ResultsEukaryotic nucleosome positioning is favored and directed by phased helical repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 62 publications
9
66
0
Order By: Relevance
“…Identical tetra-and hexamer nucleotide sequences analysis also leads to very similar conclusions, indicating robustness of these results (data not shown). Observed sequence selectivities of TrmBL2 and histones are consistent with previous experimental studies showing that archaeal nucleosomes tend to bind to G/C-rich genome regions and avoid A/T-rich transcription initiation and termination sequences (45) and that TrmBL2 protein functions as a global expression regulator of many T. kodakarensis genes by binding to some A/T-rich promoter regions (20).…”
Section: Trmbl2 and Archaeal Histones Preferentially Bind To G/crich supporting
confidence: 89%
See 1 more Smart Citation
“…Identical tetra-and hexamer nucleotide sequences analysis also leads to very similar conclusions, indicating robustness of these results (data not shown). Observed sequence selectivities of TrmBL2 and histones are consistent with previous experimental studies showing that archaeal nucleosomes tend to bind to G/C-rich genome regions and avoid A/T-rich transcription initiation and termination sequences (45) and that TrmBL2 protein functions as a global expression regulator of many T. kodakarensis genes by binding to some A/T-rich promoter regions (20).…”
Section: Trmbl2 and Archaeal Histones Preferentially Bind To G/crich supporting
confidence: 89%
“…It has been reported that T. kodakarensis histones form multimeric structures primarily in the form of tetramers binding on average to 60 bp of DNA (16,45), which is 12 times larger than a nucleotide pentamer. Therefore, 1.6 k B T energy difference per a nucleotide pentamer results in a large binding energy gap of ϳ19.2 k B T between the most and least probable histone positions on the genomic DNA.…”
Section: Trmbl2 and Archaeal Histones Preferentially Bind To G/crich mentioning
confidence: 99%
“…The binding preferences and genomic locations of stable euryarchaeal histone proteins interactions have been mapped, and it has been shown that regions directly upstream from the start codon are nucleosome depleted on a global scale (164,165). The presence of histones bound at the promoter has been correlated with a decrease in total transcription in vitro (177), and it was suggested that both steric and torsional effects limited binding of basal transcription factors to the DNA (177).…”
Section: Nucleosome Occupancy At the Promotermentioning
confidence: 99%
“…The best-described complexes are homo-or hetero-histone tetramers, homologous to the H3/H4 tetramer in eukaryotes, that associate with ϳ60 bp of double-stranded DNA. Archaeal histones share similar biases with eukaryotic nucleosomes for flexible DNA sequences and are, in general, absent from the core promoters of archaeal genes (164,165). Archaeal histone proteins share the same core fold as eukaryotic histones but lack the extensions from this fold (i.e., tails) that are highly modified and essential for proper nucleosome dynamics in eukaryotes (166).…”
Section: Chromatin Architecture Affects the Transcription Cyclementioning
confidence: 99%
See 1 more Smart Citation